Et3N/DMSO-supported one-pot synthesis of highly fluorescent β-carboline-linked benzothiophenones via sulfur insertion and estimation of the photophysical properties - Singh, Dharmender; Kumar, Vipin; Singh, Virender (Beilstein Journal of Organic Chemistry, 2020)
A robust transition-metal-free strategy is presented to access novel β-carboline-tethered benzothiophenone derivatives from 1(3)-formyl-β-carbolines using elemental sulfur activated by Et3N/DMSO. This expeditious catalyst-free reaction proceeds through the formation of β-carboline-based 2-nitrochalcones followed by an incorporation of sulfur to generate multifunctional β-carboline-linked benzothiophenones in good to excellent yields. The synthetic strategy could also be extended towards the synthesis of β-carboline-linked benzothiophenes. Moreover, the afforded products emerged as promising fluorophores and displayed excellent light-emitting properties with quantum yields (ΦF) up to 47%.
Keywords: benzothiophene; β-carboline; metal-free; photophysical properties; sulfur insertion

(untitled) - Devi, N.; Kumar, S.; Pandey, S. K.; Singh, V. (Asian J. Org. Chem., 2018)

(untitled) - Chen, Y.-F.; Kuo, P.-C.; Chan, H.-H.; Kuo, I.-J.; Lin, F.-W.; Su, C.-R.; Yang, M.-L.; Li, D.-T.; Wu, T.-S. (J. Nat. Prod., 2010)

(untitled) - Wong, S.-L.; Chang, H.-S.; Wang, G.-J.; Chiang, M. Y.; Huang, H.-Y.; Chen, C.-H.; Tsai, S.-C.; Lin, C.-H.; Chen, I.-S. (J. Nat. Prod., 2011)

(untitled) - Tran, T. D.; Pham, N. B.; Ekins, M.; Hooper, J. N. A.; Quinn, R. J. (Mar. Drugs, 2015)

(untitled) - Kumar, S.; Singh, A.; Kumar, K.; Kumar, V. (Eur. J. Med. Chem., 2017)

(untitled) - Cao, R.; Peng, W.; Wang, Z.; Xu, A. (Curr. Med. Chem., 2007)

(untitled) - Chen, H.; Gao, P.; Zhang, M.; Liao, W.; Zhang, J. (New J. Chem., 2014)

(untitled) - Zhang, M.; Sun, D. (Anti-Cancer Agents Med. Chem., 2015)

(untitled) - He, L.; Li, Y.; Tan, C.-P.; Ye, R.-R.; Chen, M.-H.; Cao, J.-J.; Ji, L.-N.; Mao, Z.-W. (Chem. Sci., 2015)

(untitled) - Ashok, P.; Ganguly, S.; Murugesan, S. (Mini-Rev. Med. Chem., 2013)

U.S. Pat. Appl. - Fourtillan, J. B.; Fourtillan, M.; Karam, O.; Zunino, F.; Jacquesy, J. C.; Tafani, J. P. (Dihydroimidazo[5,1-a]b-carboline derivatives, method for preparing same and use thereof as medicine, 2006)

(untitled) - Reixach, N.; Crooks, E.; Ostresh, J. M.; Houghten, R. A.; Blondelle, S. E. (J. Struct. Biol., 2000)

U.S. Pat. Appl. - Ostresh, J. M.; Houghten, R. A. (Combinatorial libraries of imidazol-pyrido-indole and imidazol-pyrido-benzothiophene derivatives, methods of making the libraries and compounds therein, 1999)

(untitled) - Sorbera, L. A.; Martin, L.; Leeson, P. A.; Castaner, J. (Drugs Future, 2001)

(untitled) - Daugan, A.; Grondin, P.; Ruault, C.; Le Monnier de Gouville, A.-C.; Coste, H.; Kirilovsky, J.; Hyafil, F.; Labaudinière, R. (J. Med. Chem., 2003)

(untitled) - He, L.; Liao, S. Y.; Tan, C. P.; Lu, Y. Y.; Xu, C. X.; Ji, L. N.; Mao, Z. W. (Chem. Commun., 2014)

(untitled) - Bai, B.; Shen, L.; Ren, J.; Zhu, H. J. (Adv. Synth. Catal., 2012)

(untitled) - Swami, S.; Behera, D.; Agarwala, A.; Verma, V. P.; Shrivastava, R. (New J. Chem., 2018)

(untitled) - Das, A.; Dighe, S. U.; Das, N.; Batra, S.; Sen, P. (Spectrochim. Acta, Part A, 2019)

(untitled) - Clayden, J.; MacLellan, P. (Beilstein J. Org. Chem., 2011)

Sulphur-containing drugs and related organic compounds: Chemistry, biochemistry, and toxicology - Damani, L. A. (Ellis Horwood, 1989)

(untitled) - De Oliveira Silva, A.; McQuade, J.; Szostak, M. (Adv. Synth. Catal., 2019)

(untitled) - Réamonn, L. S. S.; O'Sullivan, W. I. (J. Chem. Soc., Perkin Trans. 1, 1977)

(untitled) - Xiong, R.; Patel, H. K.; Gutgesell, L. M.; Zhao, J.; Delgado-Rivera, L.; Pham, T. N. D.; Zhao, H.; Carlson, K.; Martin, T.; Katzenellenbogen, J. A.; Moore, T. W.; Tonetti, D. A.; et al. (J. Med. Chem., 2016)

(untitled) - Malamas, M. S.; Sredy, J.; Moxham, C.; Katz, A.; Xu, W.; McDevitt, R.; Adebayo, F. O.; Sawicki, D. R.; Seestaller, L.; Sullivan, D.; Taylor, J. R. (J. Med. Chem., 2000)

(untitled) - Qin, Z.; Kastrati, I.; Chandrasena, R. E. P.; Liu, H.; Yao, P.; Petukhov, P. A.; Bolton, J. L.; Thatcher, G. R. J. (J. Med. Chem., 2007)

(untitled) - Fukuda, N.; Ikemoto, T. (Synthesis, 2015)

(untitled) - Eggers, K.; Fyles, T. M.; Montoya-Pelaez, P. J. (J. Org. Chem., 2001)

(untitled) - Steinle, W.; Rück-Braun, K. (Org. Lett., 2003)

(untitled) - Zweig, J. E.; Newhouse, T. R. (J. Am. Chem. Soc., 2017)

(untitled) - Hoffmann, K.; Guentner, M.; Mayer, P.; Dube, H. (Org. Chem. Front., 2019)

(untitled) - Jia, J.; Yu, A.; Ma, S.; Zhang, Y.; Li, K.; Meng, X. (Org. Lett., 2017)

(untitled) - Zhang, Y.; Yu, A.; Jia, J.; Ma, S.; Li, K.; Wei, Y.; Meng, X. (Chem. Commun., 2017)

(untitled) - Géant, P.-Y.; Urban, M.; Remeš, M.; Císařová, I.; Veselý, J. (Eur. J. Org. Chem., 2013)

(untitled) - Rostami, A.; Rostami, A.; Ghaderi, A. (J. Org. Chem., 2015)

(untitled) - Zheng, X.; Ding, J.; Chen, J.; Gao, W.; Liu, M.; Wu, H. (Org. Lett., 2011)

(untitled) - Yadav, M. R.; Nagaoka, M.; Kashihara, M.; Zhong, R.-L.; Miyazaki, T.; Sakaki, S.; Nakao, Y. (J. Am. Chem. Soc., 2017)

(untitled) - Yan, J.; Xu, J.; Zhou, Y.; Chen, J.; Song, Q. (Org. Chem. Front., 2018)

(untitled) - Zheng, G.; Ma, X.; Liu, B.; Dong, Y.; Wang, M. (Adv. Synth. Catal., 2014)

(untitled) - Wang, X.; Gensch, T.; Glorius, F. (Org. Chem. Front., 2016)

(untitled) - Xia, X.-F.; He, W.; Zhang, G.-W.; Wang, D. (Org. Chem. Front., 2019)

(untitled) - Nguyen, T. B. (Adv. Synth. Catal., 2017)

(untitled) - Huang, Y.; Zhou, P.; Wu, W.; Jiang, H. (J. Org. Chem., 2018)

Sulfur Chemistry - Jiang, X. (Springer, 2019)

(untitled) - Wang, M.; Dai, Z.; Jiang, X. (Nat. Commun., 2019)

(untitled) - Wang, M.; Fan, Q.; Jiang, X. (Org. Lett., 2016)

(untitled) - Ohmoto, T.; Koike, K. (Chem. Pharm. Bull., 1984)

(untitled) - Singh, D.; Tiwari, S. K.; Singh, V. (New J. Chem., 2019)

(untitled) - Singh, D.; Devi, N.; Kumar, V.; Malakar, C. C.; Mehra, S.; Rattan, S.; Rawal, R. K.; Singh, V. (Org. Biomol. Chem., 2016)

(untitled) - Devi, N.; Singh, D.; Honey, H.; Mor, S.; Chaudhary, S.; Rawal, R. K.; Kumar, V.; Chowdhury, A. K.; Singh, V. (RSC Adv., 2016)

(untitled) - Devi, N.; Singh, D.; Kaur, G.; Mor, S.; Putta, V. P. R. K.; Polina, S.; Malakar, C. C.; Singh, V. (New J. Chem., 2017)

(untitled) - Singh, D.; Devi, N.; Kumar, V.; Malakar, C. C.; Mehra, S.; Rawal, R. K.; Kaith, B. S.; Singh, V. (RSC Adv., 2016)

(untitled) - Singh, D.; Hazra, C. K.; Malakar, C. C.; Pandey, S. K.; Kaith, B. S.; Singh, V. (ChemistrySelect, 2018)

(untitled) - Singh, D.; Sharma, P.; Kumar, R.; Pandey, S. K.; Malakar, C. C.; Singh, V. (Asian J. Org. Chem., 2018)

(untitled) - Singh, D.; Kumar, V.; Devi, N.; Malakar, C. C.; Shankar, R.; Singh, V. (Adv. Synth. Catal., 2017)

(untitled) - Singh, D.; Sharma, S.; Kumar, M.; Kaur, I.; Shankar, R.; Pandey, S. K.; Singh, V. (Org. Biomol. Chem., 2019)

(untitled) - Meunier, B. (Acc. Chem. Res., 2008)

(untitled) - Abdolmaleki, A.; Ghasemi, J. B. (Curr. Top. Med. Chem., 2017)

(untitled) - Nguyen, T. B.; Retailleau, P. (Org. Lett., 2018)

(untitled) - Nguyen, T. B.; Retailleau, P. (Org. Lett., 2017)

(untitled) - Nguyen, T. B.; Retailleau, P. (Org. Lett., 2017)

(untitled) - Singh, M.; Awasthi, P.; Singh, V. (Eur. J. Org. Chem., 2020)

(untitled) - Kumar, V.; Singh, D.; Paul, A. K.; Shrivastava, R.; Singh, V. (New J. Chem., 2019)

(untitled) - Sangeetha, S.; Sekar, G. (Org. Lett., 2017)

(untitled) - Sangeetha, S.; Muthupandi, P.; Sekar, G. (Org. Lett., 2015)

(untitled) - Hayashi, Y. (Chem. Sci., 2016)

(untitled) - Battini, N.; Padala, A. K.; Mupparapu, N.; Vishwakarma, R. A.; Ahmed, Q. N. (RSC Adv., 2014)

(untitled) - Mori, T.; Hoshino, S.; Sahashi, S.; Wakimoto, T.; Matsui, T.; Morita, H.; Abe, I. (Chem. Biol., 2015)

(untitled) - Zhang, G.; Yi, H.; Chen, H.; Bian, C.; Liu, C.; Lei, A. (Org. Lett., 2014)

(untitled) - Liu, J.; Liu, C.; He, W. (Curr. Org. Chem., 2013)

(untitled) - Demas, J. N.; Crosby, G. A. (J. Phys. Chem., 1971)

(untitled) - Pardo, A.; Reyman, D.; Poyato, J. M. L.; Medina, F. (J. Lumin., 1992)

(untitled) - Rasmussen, S. C.; Sattler, D. J.; Mitchell, K. A.; Maxwell, J. (J. Lumin., 2004)

(untitled) - Fujitsuka, M.; Sato, T.; Sezaki, F.; Tanaka, K.; Watanabe, A.; Ito, O. (J. Chem. Soc., Faraday Trans., 1998)